DISCOURSE AND ITS PRIVILEGE IN TEXT FORMATION - Botirov Abdumalik Rejabovich (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The following article discusses the term discourse in deeper sense by emphasizing the advantages of this concept in construction of text. There is given the thoughts of different linguists whose majoring field lay around this topic. Authors also points out some discursive markers that help the communication be quite natural.